Jesus’ Discipleship and the Failure of the Disciples in the Gospel of Mark according to Dietrich Bonhoeffer - Emilia Kartika; Hiu Willison; David Sulardi Sastro; Yosef Antonius (Asian Journal of Philosophy and Religion, 2026)
This article examines Jesus’ discipleship in the Gospel of Mark by foregrounding the disciples’ failure as integral to the formation process. Contemporary church practices often reduce discipleship to doctrinal instruction and measurable outcomes, resulting in a fragmented understanding of Christian formation. Using qualitative library research, this study analyzes key Markan narratives in dialogue with Dietrich Bonhoeffer’s theology of Nachfolge. The findings show that failure is not a disruption but a formative space sustained by Jesus’ faithful presence. This study offers a theological corrective to success-oriented models of discipleship and proposes a relational, process-oriented framework, contributing to biblical studies and practical theology by reframing failure as essential to authentic Christian formation.